Takotsubo Cardiomyopathy in the setting of Urosepsis - Saraf, Awin; Hirachan, Anish; Sharma, Ranjit (Nepalese Heart Journal, 2023)
Takotsubo cardiomyopathy is a rare cardiac condition associated with transient left ventricular apical wall motion abnormalities in association with stress but without any signifcant coronary artery disease. We present a case of takotsubo cardiomyopathy presenting as acute pulmonary edema in the background of urosepsis.